2014
DOI: 10.1590/s1415-43662014000600010
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de propriedades hidrodinâmicas de um Neossolo Regolítico sob pastagem e caatinga

Abstract: R E S U M OAs propriedades hidrodinâmicas dos solos de pastagem e de caatinga, são afetadas por diversos fatores, sobretudo associados a aspectos espaciais e temporais relacionados às diferentes características dos sistemas radiculares e das taxas de pisoteio do gado, mas poucos resultados que avaliem o efeito da magnitude dessas fontes de variabilidade sobre as propriedades hidrodinâmicas dos solos têm sido relatados na literatura. Objetivou-se analisar a variabilidade espacial dos parâmetros que descrevem as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
2
11
1
3
Order By: Relevance
“…However, the slight increase in soil density in the PD area led to low values of saturated hydraulic conductivity, sorption and infiltration (Table 2). Contrary to the results found for soil bulk density for the study, Oliveira Júnior et al (2014) verified that soil management with pasture significantly altered the soil density, which for the pasture was 1.39 g cm -3 and for the Caatinga vegetation was 1.30 g cm -3 , proving that the intensive use of these grazing areas promotes changes in the physical characteristics of the soil.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…However, the slight increase in soil density in the PD area led to low values of saturated hydraulic conductivity, sorption and infiltration (Table 2). Contrary to the results found for soil bulk density for the study, Oliveira Júnior et al (2014) verified that soil management with pasture significantly altered the soil density, which for the pasture was 1.39 g cm -3 and for the Caatinga vegetation was 1.30 g cm -3 , proving that the intensive use of these grazing areas promotes changes in the physical characteristics of the soil.…”
Section: Resultscontrasting
confidence: 75%
“…According to Oliveira Júnior et al (2014), the sorptivity translates the capacity of the soil to absorb water by capillarity and depends essentially on the variation of the volumetric water content between the beginning and the end of the infiltration. These same authors also contacted reductions in Ksat and S in pasture area, with a reduction of 20% when compared to soil under Caatinga vegetation for S. According to Parente et al (2010), a well-structured, less compacted soil can have higher values of sorptivity and hydraulic conductivity and, due to the organic matter content, can retain more water.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazilian soil physics literature, several authors relate the inverse of parameter α to the air-entry pressure, in analogy to the BC parameter h b . Some use this kind of identification when describing VG parameters (Souza et al, 2008a;Lima et al, 2014;Oliveira Júnior et al, 2014), others when explicitly interpreting results of α values to the air-entry pressure (Souza et al, 2008b;Silva et al, 2009;Mota et al, 2017). In international literature, a similar description can sometimes be found (Pollaco and Mohanty, 2012;Aschonitis and Antonopoulos, 2013;Aschonitis et al, 2015;Dokoohaki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…15 n. 2, e2368 -Taubaté 2020 as well as inspiring alternative guidelines for more integrated plans that combat desertification. Oliveira Junior et al (2014) evaluated the impact of pasture on the hydrodynamic properties of a regolithic neo-soil in the Agreste Region of Pernambuco, and observed that the use of the soil for pastureland significantly altered its properties when compared with those of the natural Caatinga soil, mainly with regard to soil density and hydraulic conductivity.…”
Section: Introductionmentioning
confidence: 99%